2007
DOI: 10.1136/bmj.39315.670208.47
|View full text |Cite
|
Sign up to set email alerts
|

Changes in exposure of adult non-smokers to secondhand smoke after implementation of smoke-free legislation in Scotland: national cross sectional survey

Abstract: OBJECTIVE To measure change in adult non-smokers' exposure to secondhand smoke in public and private places after smoke-free legislation was implemented in Scotland. DESIGN Repeat cross sectional survey. SETTING Scotland. PARTICIPANTS Scottish adults, aged 18 to 74 years, recruited and interviewed in their homes. INTERVENTION Comprehensive smoke-free legislation that prohibits smoking in virtually all enclosed public places and workplaces, including bars, restaurants, and cafes. OUTCOME MEASURES Salivary cotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
2
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 24 publications
9
138
2
11
Order By: Relevance
“…Our analyses were complicated by the fact that (a) some municipalities within provinces/states had their own comprehensive smoke-free laws, (b) presence/absence of comprehensive smoke-free laws was highly correlated with country of residence, and (c) states/provinces had laws in place for varying lengths of time (anywhere from at the outset of survey to more than 5 years before the survey), this weakens the strength of conclusions that can be drawn. Additionally, a 2007 longitudinal study conducted in Scotland found no changes in nonsmoking adults and children's exposure to cigarette smoke in cars after the introduction of comprehensive smoke-free legislation (Akhtar et al, 2007;Haw & Gruer, 2007). However, the utility of comprehensive smoke-free legislation for promoting smokefree cars should not be discounted; previous studies have linked comprehensive smoke-free legislation with the implementation of smoke-free homes, and our study found that smokers with smoke-free homes are less likely to smoke in cars with nonsmokers (Borland et al).…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses were complicated by the fact that (a) some municipalities within provinces/states had their own comprehensive smoke-free laws, (b) presence/absence of comprehensive smoke-free laws was highly correlated with country of residence, and (c) states/provinces had laws in place for varying lengths of time (anywhere from at the outset of survey to more than 5 years before the survey), this weakens the strength of conclusions that can be drawn. Additionally, a 2007 longitudinal study conducted in Scotland found no changes in nonsmoking adults and children's exposure to cigarette smoke in cars after the introduction of comprehensive smoke-free legislation (Akhtar et al, 2007;Haw & Gruer, 2007). However, the utility of comprehensive smoke-free legislation for promoting smokefree cars should not be discounted; previous studies have linked comprehensive smoke-free legislation with the implementation of smoke-free homes, and our study found that smokers with smoke-free homes are less likely to smoke in cars with nonsmokers (Borland et al).…”
Section: Discussionmentioning
confidence: 99%
“…2,22,23,29,[34][35][36][37][38][39][40] Nevertheless, some findings suggest that smoking bans may have negative repercussions. 4,41,42 The relationships between private and public spaces with regard to smoking bans and behavior have been found to be complex and have been said to "demand[] more consideration if interventions in public areas are meant to serve as catalysts for favorable changes in primary private spaces such as homes."…”
Section: Effects Of Enactment Of Legislative (Public)mentioning
confidence: 99%
“…26 A second, somewhat more pessimistic, theoretical model is that of displacement or last refuge which posits that smoking bans in public places will displace smoking behaviors to private places, like homes, and will produce undesired effects such as increased SHS exposure for nonsmoking family members. 3,29 This is especially concerning for children, who are more vulnerable to the effects of SHS. 5,30,31 In the United States, in 2010, approximately 98% of children living with a smoker, compared to 40% not living with a smoker, had cotinine levels (a metabolite of nicotine which has a longer half-life than nicotine) above .05 ng/mL, indicating SHS exposure.…”
Section: Effects Of Enactment Of Legislative (Public)mentioning
confidence: 99%
“…[59][60][61] Nonrandomised designs may have to be used for studying rare adverse events, which a trial would have to be implausibly large to detect. 62 63 An example is the use of case-control methods to evaluate the impact on the incidence of sudden infant deaths of advice about sleep position and other aspects of babies' sleeping environment.…”
mentioning
confidence: 99%